Good practice guide to setting inputs for operational risk models. (9th November 2016) - Kelliher, P. O. J.; Acharyya, M.; Couper, A.; Grant, K.; Maguire, E.; Nicholas, P.; Smerald, C.; Stevenson, D.; Thirlwell, J.; Cantle, N.
Abstract: This paper seeks to establish good practice in setting inputs for operational risk models for banks, insurers and other financial service firms. It reviews Basel, Solvency II and other regulatory requirements as well as publicly available literature on operational risk modelling. It recommends a combination of historic loss data and scenario analysis for modelling of individual risks, setting out issues with these data, and outlining good practice for loss data collection and scenario analysis. It recommends the use of expert judgement for setting correlations, and addresses information requirements for risk mitigation allowances and capital allocation, before briefly covering Bayesian network methods for modelling operational risks.